Tubal pregnancy in a case of unicornuate uterus with contralateral streak ovary and renal agenesis: A case report - Lauren H. Barnts; Taylor J. Kratochvil; Sylvia J. Ziegenbein (Elsevier, 2022)
A 24-year-old woman presented to the emergency department with symptoms consistent with an ectopic pregnancy. Ultrasonographic evaluation reported no evidence of intrauterine pregnancy, a heterogenous mass in the left adnexa, and normal-appearing bilateral ovaries. The right kidney was imaged, though the left kidney was not visualized. Beta-HCG was reported below the discriminatory zone. Two days later, her ultrasound remained unchanged, and beta-HCG had not risen appropriately. Diagnostic laparoscopy revealed a dilated right fallopian tube with products of conception exuding from the fimbriated end. Laparoscopically, the patient's pelvic anatomy was found to be abnormal. There was no left fallopian tube and the uterus appeared unicornuate with absent left horn. A left streak ovary was present superior to the pelvic brim in the pericolic gutter, though the right ovary appeared normal and in the appropriate position. At follow-up, hysterosalpingography showed a right-sided unicornuate uterus without septation, a small tubular endometrial cavity, and a patent right fallopian tube. Defects of unification of the Mullerian ducts, such as unicornuate uterus, do not reduce the ability to achieve pregnancy, but do increase the risk of adverse outcomes and fetal malpresentation.